Happiness and social determinants across age cohorts in Taiwan. (September 2016) - Hsu, Hui-Chuan; Chang, Wen-Chiung; Chong, Young-Sook; An, Jeong Shin
The purpose of this study was to examine happiness and social determinants across age cohorts in Taiwan. The data were obtained from the 2011 Taiwan Social Change Survey (aged 18 +, n = 2, 199). The social determinants of happiness included socioeconomic status and social connection. Happiness was not different across the age groups. Receiving less family support, less formal support, more social trust and more control over life were significant for the younger group. Being married and having more social participation were significant for the middle-aged. Receiving less family support and having a higher economic status were significant for the older group.